ASYMMETRIC RELATIONSHIP BETWEEN OIL PRICE AND EXCHANGE RATE: THE CASE OF ROMANIA - Taşar, İzzet (My University, 2018)
The fragile structure of the global economy in the last decades makes it necessary for policy makers tohave consistent predictions on the future values of the commodities and assets and also exchange rates. Thefact that it is still the biggest source of energy, oil, has a crucial importance for the real economy and evenfinancial markets. In this study, the relation of the real oil price and the real exchange rate in Romania will beinvestigated for the period of 2004:4 to 2014:10 using monthly data. Results in the tests suggest thatRomania should consider the real oil price and real exchange rate causality due to the fact that there is asignificant causality between the variables.
Keywords: Mühendislik; Petrol; İktisat